Functional study of Bergeyella cardium KP-43 subfamily peptidases as putative T9SS cargo - Tian Li; Yiwen Gao; Xiaoyue Zhang; Yuxiao Zhao; Fuyao Hu; Wei Li; Lixiang Li; Hongwei Pan; Yi Zhang; Ying Chen (Communications Biology)
Abstract Bergeyella cardium causes infections in human organs. However, the mechanism of the virulence of B. cardium is unclear. Peptidases are important virulence factors in bacterial pathogens. Here, we identified three KP-43 subfamily peptidases, SpBcA, SpBcB and SpBcC, which are putative T9SS cargo proteins, and analyzed their protease activity. SpBcA and SpBcB are active in vitro and contain a propeptide that passes through the active site of the S8 peptidase domain and inhibits its activity. SpBcA activates itself by cleaving the propeptide at N102 within the TSNA (100–103) peptide and a putative cleavage site at 116–120 (TSPGL). Additionally, SpBcA degrades host defense molecules, fibrinogen, antimicrobial peptide LL-37 and gelatin in vitro and induces cell death in vivo, suggesting its role as a virulence factor. This study revealed the self-cleavage regulatory mechanism of SpBcA and provided a basis for studying how B. cardium uses peptidases as virulence factors in vivo.